The Model of the Formation of Professional Training of Future Social Pedagogy Teachers in the Conditions of the University - Menlibekova, G.; Zhumankulova, E.; Kurmankulov, A.; Ybray, S.; Balazhanova, K.; Gulmira, Tussupbekova (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Scientific and technical progress in era of globalization, as well as socio-economic changes occurring in the global world requires the enhancement in the field of science, education, and culture also lead to the innovations on pedagogical science, modern school, and the development of the teacher personality. The school faces the task of forming a comprehensive and harmoniously developed personality. Along with this, the vocational orientation of the student's personality already at the school level becomes most relevant, especially with the introduction of a 12-year education at school. Among all above mentioned, a special place is given to a social pedagogue's personality, since his professional activity acquires qualitatively new characteristics. Social pedagogue is a link between the school and other institutions, between parents and students, and can carry out their work in multifunctional areas such as socio-pedagogical, psychological-pedagogical, socio-legal and socio-economic sphere. Social pedagogue should also assist students in the professional orientation to develop themselves in competitive environment. This research aims to analyze the formation of professional training of future social pedagogy teachers in the conditions of the University. And in order to achieve this goal to do some tasks. We need to describe the process of professional training of teachers and do research on its condition at the university level. All these areas contain various aspects of the activity, and the preparation of future social teachers at the university level should be systematic, practice-oriented, and carried out at the very early stages of preparation at the University. Accordingly, the requirements for the quality of training should also change.